2015
DOI: 10.1016/j.jspd.2014.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Sagittal Spinopelvic Parameters in Scheuermann's Kyphosis: A Preliminary Study

Abstract: Sagittal pelvic alignment in patients with SK is not different from that in normal subjects. Furthermore, in SK thoracic kyphosis did not correlate with any distal region of the spine (lumbar or pelvic). Further understanding of the relationship between sagittal spinopelvic alignment in various conditions causing spinal deformity will lead to better treatment of these conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 24 publications
2
6
0
4
Order By: Relevance
“…These are consistent with the previous reports by Mac-Thiong et al, 18 who described average values of PI, PT and SS as 49°, 8°and 41°r espectively, for normal children and adolescents. These observations are consistent with those of the study published by Cahill et al, 19 who evaluated the differences in spinopelvic parameters among patients with SK and unaffected normal controls, allowing us to conclude that there was no statistically significant difference in the pelvic parameters. Therefore, this suggests that SK is not driven by an inherent problem in the pelvic anatomy resulting in abnormal mechanics in the thoracic or thoracolumbar spine with subsequent secondary vertebral wedging, but rather that the anatomic changes observed at the apex of the deformity in SK are in fact the primary pathologic process.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These are consistent with the previous reports by Mac-Thiong et al, 18 who described average values of PI, PT and SS as 49°, 8°and 41°r espectively, for normal children and adolescents. These observations are consistent with those of the study published by Cahill et al, 19 who evaluated the differences in spinopelvic parameters among patients with SK and unaffected normal controls, allowing us to conclude that there was no statistically significant difference in the pelvic parameters. Therefore, this suggests that SK is not driven by an inherent problem in the pelvic anatomy resulting in abnormal mechanics in the thoracic or thoracolumbar spine with subsequent secondary vertebral wedging, but rather that the anatomic changes observed at the apex of the deformity in SK are in fact the primary pathologic process.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, this suggests that SK is not driven by an inherent problem in the pelvic anatomy resulting in abnormal mechanics in the thoracic or thoracolumbar spine with subsequent secondary vertebral wedging, but rather that the anatomic changes observed at the apex of the deformity in SK are in fact the primary pathologic process. 19 The postoperative SB is an important predictor of functional results when depicting the muscular forces acting on the spine and the associated energy spent. 20 In the present study, the mean values of the SB remained within the normal range before and after surgery, which was also described by Guler et al 21 after surgical correction of SK.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different studies about Scheuermann kyphosis question these relationships especially between PI and LL, whereas these 2 parameters have been shown to be key factors to account for in achieving good clinical results. 18,23 On the other hand, Ashraf et al 3 and Cahill et al 24 showed in their studies that LL is driven by hyperkyphosis elsewhere. The latter suggest that the lumbar spine serves as a sagittal buffer between the pelvis and thoracic spine.…”
Section: Discussionmentioning
confidence: 99%